Combined chemically enhanced primary sedimentation and biofiltration process for low cost municipal wastewater treatment. Issue 12 (15th October 2019) - Bezirgiannidis, Athanasios; Plesia-Efstathopoulou, Aikaterini; Ntougias, Spyridon; Melidis, Paraschos
Abstract: The main objective of wastewater treatment is to remove carbon and other nutrients from municipal and industrial effluents in order to protect the environment and human health. Typical wastewater treatment is usually achieved by a combination of physical, chemical and biological methods. In this work, municipal wastewater was depurated using chemically enhanced primary treatment (CEPT) in combination with a pilot-scale trickling filter. Lab scale experiments (Jar-tests) were carried out in order to determine the optimum dosage of chemicals. Selection criteria were the organic load removal efficiency and the low operational cost. Coagulation-flocculation process was conducted through polyaluminium chloride (PAC) and the cationic polyelectrolyte (Zetag 8180) addition. By combining CEPT and trickling filter, tCOD (total Chemical Oxygen Demand), sCOD (soluble Chemical Oxygen Demand), BOD5 (5-day Biochemical Oxygen Demand), NH4 + -N, TSS (Total Suspended Solids), VSS (Volatile Suspended Solids) and PO4 3− -P removal efficiencies were estimated to be 89, 82, 93, 60, 96, 96 and 78%, respectively. It is concluded that biological filtration contributed significantly in nutrients removal processes. Moreover, the obtained effluent was low in carbon and rich in nitrogen, which can be applied for restricted irrigation after disinfection, complying with the discharge limits set in the Greek Joint Ministerial Decree 145116/2011.